مدى فاعلية نظام (الموودل) في تنفيذ البرامج التدريبية لموظفي وزارة التربية والتعليم في سلطنة عمان من وجهة نظر المتدربين والقائمين عليه - رواحي، عبد الباسط سعيد
This study aimed to identify the factors influencing the use of the electronic training platform (Moodel) in the Ministry of Education in Oman, and to measure the extent to which each of the factors affecting it is related using the theories TAM and EDT and the updated model of (delene and mclean 2003) The researcher took the random class sample from the study community (trainees on the moodl system) and took their opinions by means of the resolution tool, which was divided into nine paragraphs, eight of which were for the factors affecting (expected benefit, ease of use, technical support, quality of information, quality of service, quality of service, quality of service). The system, trust, satisfaction and factor IX are the factor influencing the use factor, thus including the total number of questions in the questionnaire forty-six questions designed on the Likert scale. Based on previous studies on the effectiveness of the e-training system (moodel) and the existence of the study problem, the researcher took the authors of the e-training project as another community in the study to understand the dimensions of the problem and to find the best solutions to it. Hence, the interview tool was the best for the sample of the small community. The researcher will interview three community researchers. The interview questions are tailored to the PMP (Project Management Professional) criteria, which include the project's four lives: (planning, construction, application, closing). In the fourth chapter, the researcher reviewed the analysis of the data obtained from the resolution and corresponding instruments. Before analyzing the data resolution number of the sample number of 349 researchers the researcher examined the data and searched for lost values, then searched for extreme values, whether positive or negative, as well as ensuring that the data were distributed naturally and a linear evaluation of the data, and the researcher was assured that there were no correlation values between the independent variables exceeding the permissible limit after examining the matrix of correlation between independent variables, after examining the matrix of correlation between independent variables, then the researcher conducted a demographic analysis of the sample and among them the gender of 123 males and females 226. The researcher analyzed the paragraphs of the study tool by calculating the number of repetitions and the percentage of each level of the study sample answer scoring according to the Penkert penta meter. The researcher found in the general analysis of the axes of the study that the expected benefit of using the moodil system is the most important factor that drives trainees to use the moodil system, because they are looking for the benefit that enables them to develop their skills and abilities in order to develop their performance. The researcher used pearson's test to analyze the relationship between variables and the results of the study hypotheses indicated a strong relationship between the variables most often. The researcher analyzed the interview by emptying the questions and answers of the interview in a table for each of the three researchers, and then analyzed the answers of the researchers, which concluded that there is no clear and scheduled plan and that the tasks do not proceed sequentially as assumed according to the criteria of project management with a lack of expertise and training of existing cadres for the project.